2015
DOI: 10.1007/s10552-015-0641-1
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and risk of colorectal cancer: results from the CLUE II cohort and a meta-analysis of prospective studies

Abstract: Purpose The association between prediagnostic inter-leukin-6 (IL-6) concentrations and risk of colorectal cancer was evaluated in a nested case–control study and a meta-analysis of prospective studies. Methods Colorectal cancer cases (n = 173) and matched controls (n = 345) were identified between 1989 and 2000 among participants in the CLUE II cohort of Washington Country, Maryland. Matched odds ratios and the corresponding 95 % confidence intervals (CIs) were estimated using conditional logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
40
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 37 publications
(56 reference statements)
10
40
1
1
Order By: Relevance
“…The totality of the current evidence, as summarized in previous meta-analyses, suggests that CRP is weakly associated with an increased risk for colorectal cancer 23,24 . Our null association between plasma IL-6 level and colorectal cancer risk was consistent with conclusions from most previous published prospective studies 9,12,13,25 , and meta-analyses 24,25 . In one study, IL-6 levels were associated with colorectal cancer risk, but the association did not remain significant after further adjustment for insulin 20 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The totality of the current evidence, as summarized in previous meta-analyses, suggests that CRP is weakly associated with an increased risk for colorectal cancer 23,24 . Our null association between plasma IL-6 level and colorectal cancer risk was consistent with conclusions from most previous published prospective studies 9,12,13,25 , and meta-analyses 24,25 . In one study, IL-6 levels were associated with colorectal cancer risk, but the association did not remain significant after further adjustment for insulin 20 .…”
Section: Discussionsupporting
confidence: 92%
“…Of note, in the Health Professionals Follow-up Study, there was a significant association of IL-6 with colorectal cancer among lean men17, which was not observed in this study. Lastly, data from the prospective CLUE II cohort suggest that there is a significant association between IL-6 levels and risk of colon cancer 25 . While our study did not confirm this finding, more prospective research is required to determine whether plasma IL-6 levels are associated with colon cancer risk.…”
Section: Discussionmentioning
confidence: 97%
“…Results for mediation by inflammatory biomarkers were weaker for all analyses, despite the fact that adiposity is associated with low‐grade systemic inflammation, and that systemic inflammation has been linked to CRC risk, though inconsistently. Several studies, have observed null or weak associations between many of these circulating inflammatory biomarkers and CRC risk, while other studies have observed positive associations . Notably, in exploratory subgroup analyses, we observed qualitatively stronger mediation by the biomarkers among nonusers of NSAIDs/aspirin compared to regular users, although these analyses were low in power.…”
Section: Discussioncontrasting
confidence: 80%
“…Interleukin‐6 (IL‐6) is a cytokine involved in many proinflammatory pathways of the immune response . We reported a positive association between plasma IL‐6 concentration and risk of colon cancer in this cohort, and presented a meta‐analysis of six prospective studies that provided support for a modest positive association between IL‐6 concentrations and colon cancer risk . In the present study, we identified a borderline inverse association between a candidate SNP in IL6 (rs1800797) and adenomas and, among leaner individuals only, a positive association between a different candidate SNP in IL6 (rs1800796) and adenomas.…”
Section: Discussionsupporting
confidence: 50%